Enrichment of Ly6Chi monocytes by multiple GM-CSF injections with HBV vaccine contributes to viral clearance in a HBV mouse model. Issue 12 (2nd December 2017) - Zhao, Weidong; Zhou, Xian; Zhao, Gan; Lin, Qing; Wang, Xianzheng; Yu, Xueping; Wang, Bin
ABSTRACT: Adjuvants are considered a necessary component for HBV therapeutic vaccines but few are licensed in clinical practice due to concerns about safety or efficiency. In our recent study, we established that a combination protocol of 3-day pretreatments with GM-CSF before a vaccination (3 × GM-CSF+VACCINE) into the same injection site could break immune tolerance and cause over 90% reduction of HBsAg level in the HBsAg transgenic mouse model. Herein, we further investigated the therapeutic potential of the combination in AAV8–1.3HBV-infected mice. After 4 vaccinations, both serum HBeAg and HBsAg were cleared and there was a 95% reduction of HBV-positive hepatocytes, in addition to the presence of large number of infiltrating CD8 + T cells in the livers. Mechanistically, the HBV-specific T-cell responses were elicited via a 3 × GM-CSF+VACCINE-induced conversion of CCR2-dependent CD11b + Ly6C hi monocytes into CD11b + CD11c + DCs. Experimental depletion of Ly6C hi monocytes resulted in a defective HBV-specific immune response thereby abrogating HBV eradication. This vaccination strategy could lead to development of an effective therapeutic protocol against chronic HBV in infected patients.